Lukashov O.O. Foreign experience of designing effective governmental regulation of the strategic regional development: combining theory and practice - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
The paper summarizes foreign experience of designing more effective and  exible mechanisms of governmental regulation of a regional strategic development through a critical re ection of modernexisting theory and practice-based conclusions. Relying on this, author’s generalization of managerial “traps” and potential solutions and mechanisms with the optimal strategic development of the modern Ukrainian region are proposed.